2021
DOI: 10.21111/at-tadib.v16i2.6736
|View full text |Cite
|
Sign up to set email alerts
|

Character Development Based on Hybrid Learning in the Post-Pandemic Era

Abstract: Corona Virus Disease 19 is currently a global virus outbreak and impacts the order of life, including education. The Covid-19 virus pandemic, the lecture system or learning from conventional was shifted to super-high technology to innovate learning models, including the Hybrid Learning model. The innovation of the face-to-face learning model (PTM) Hybrid Learning is based on character aspects. It uses health protocol tools such as hand sanitizer, masks with 3 or 4 layers according to health regulations, and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Accordingly, combining learning technology and cloud information can support the learning process in the classroom, where various studies have found that the hybrid format is effective as a distance learning mode for university students (Manciaracina, 2020;Masalimova et al, 2021;Wijaya & Budiman, 2021). The results of this study also confirm that colleges and universities need to start extending the application of digital learning environments and hybrid learning methods to serve as alternative modes.…”
Section: E Discussionsupporting
confidence: 64%
“…Accordingly, combining learning technology and cloud information can support the learning process in the classroom, where various studies have found that the hybrid format is effective as a distance learning mode for university students (Manciaracina, 2020;Masalimova et al, 2021;Wijaya & Budiman, 2021). The results of this study also confirm that colleges and universities need to start extending the application of digital learning environments and hybrid learning methods to serve as alternative modes.…”
Section: E Discussionsupporting
confidence: 64%
“…Therefore, every tertiary institution must have an LMS as a media and teaching resource for lectures. Essentially, hybrid learning must take place in a virtual interactive discussion while instilling character values that are integrated into the hybrid lecture model [48]. Of course, student involvement is critical for the realization of effective hybrid learning, so that students do more than just study electronic teaching materials, but also interact intensively with lecturers or peers [49].…”
Section: Evaluation Of Hybrid Learning Input In Higher Educationmentioning
confidence: 99%
“…If the character guidelines have penetrated a person's soul and become a system in all his behavior in life, then that one person has the title "human with character." (Wijaya and Budiman 2021); (Wijaya and Yusuf 2021); (Yusuf et al 2021).…”
Section: Types Of Spiritual Values That Should Be Instilled In Genera...mentioning
confidence: 99%